Arsenic speciation and distribution in industrially polluted estuarine sediments and their effects on bacterial communities - Liu, Sijia; Yu, Xiaoman; Zhao, Haodong; Dai, Quanyu (Frontiers in Microbiology, 2025)
Industrial wastewater is a significant contributor to coastal pollution. Heavy metal contamination poses a substantial risk to the ecological integrity of an area by altering the structure and function of bacterial communities. This study systematically analyzed the distribution of total and arsenic (As) fractions in surface and sediment profiles, as well as the response of bacterial communities to As contamination in industrially polluted estuarine areas. The results revealed significant spatial variability in As concentrations across the sampling sites, with the highest As level detected at the sewage discharge outlet, reaching 979.05 ± 106.17 mg/kg. A pronounced decline in total As (T-As) concentrations was observed with increasing sediment depth, underscoring the predominant contribution of industrial emissions to sedimentary As accumulation. A significant positive correlation between As and iron (Fe) suggested that As retention was likely to be primarily associated with amorphous Fe minerals. Notably, bioavailable As (B-As) constituted 72.92 ± 4.15% of the T-As in sediments, highlighting its potential ecological impact. Further analysis demonstrated that T-As, B-As, and strongly adsorbed As (AsPO4) were key determinants of bacterial community diversity and composition. It also found that sediment As levels correlated significantly with the abundance of a major bacterial phylum, the expression of arsenic resistance genes, and the functional potentials of bacterial communities involved in nitrogen (N), sulfur (S), and phosphorus (P) cycling. Overall, this study shows that As contamination in industrially polluted estuarine areas exerts a profound influence on the abundance, diversity, and functional potential of bacterial communities.